Dynamic insertion of Pot3 in AvrPib prevailing in a field rice blast population in the Philippines led to the high virulence frequency against the resistance gene Pib in rice - Olukayode, Toluwase; Quime, Berlaine; Shen, Yin-Chi; Yanoria, Mary Jeannie; Zhang, Suobing; Yang, Jianyuan; Zhu, Xiaoyuan; Shen, Wei-Chiang; von Tiedemann, Andreas; Zhou, Bo (Scientific Societies, 2019)
The Magnaporthe oryzae avirulence gene AvrPib is required for the resistance mediated by its cognate resistance gene Pib, which has been intensively used in indica rice breeding programs in many Asian countries. However, the sequence diversity of AvrPib among geographically distinct M. oryzae populations was recently shown to be increasing. Here, we selected a field population consisting of 248 rice blast isolates collected from a disease hotspot in Philippine for the analysis of AvrPib haplotypes and their pathogenicity against Pib. We found that all of the isolates were virulent to Pib and each of them contained an insertion of Pot3 transposon in AvrPib. Moreover, Pot3 insertion was detected in different genomic positions, resulting in three different AvrPib haplotypes, designated avrPib-H1 to H3. We further conducted a genome-wide Pot2 fingerprinting analysis by repetitive element palindromic polymerase chain reaction (PCR) and identified seven different lineages out of 47 representative isolates. The isolates belonging to the same lineage often had the same AvrPib haplotype. In contrast, the isolates having the same AvrPib haplotypes did not always belong to the same lineages. Both mating types MAT1-1 and MAT1-2 were identified in the population in Bohol and the latter appeared dominant. On the host side, we found that 32 of 52 released rice varieties in the Philippines contained Pib diagnosed by PCR gene-specific primers and DNA sequencing of gene amplicons, suggesting that it was widely incorporated in different rice varieties. Our study highlights the genetic dynamics of rice blast population at both the AvrPib locus and the genome-wide levels, providing insight into the mechanisms of the mutations in AvrPib leading to the breakdown of Pib-mediated resistance in rice.